Indian Diaspora Gastronomy: On the Changing Use of Herbs and Spices Among Southern California's Indian Immigrant Women - Joseph, Elois; Voeks, Robert (Frontiers in Sustainable Food Systems, 2021)
Southern California has witnessed a burgeoning Indian immigrant population in recent decades. And among the cultural features that most distinguishes Indians is their cuisine. Their use of herbs and spices in food and medicine, in particular, is tightly bound to language, religion, gender, and overall cultural identity. Identifying how Indian immigrants' culinary choices adapt to southern California's varied and often fast-food based gastronomy, particularly impacts on the inter-generational transmission of traditional culinary knowledge, is important in terms of understanding the role of cultural retention and assimilation, as well as culturally-defined notions of food in physical and psychological well-being. We explored these questions by means of interviews with 31 Indian immigrant women in southern California. Participants were selected by means of snowball sampling. Our working hypothesis was that problems with sourcing and cultural assimilation pressures would have eroded the use of traditional herbs and spices. A total of 66 herbs and spices (and associated seasonings) were reported. Of these, the highest frequency of use was recorded for turmeric (100% of respondents) followed by cilantro, cinnamon, clove, cumin, curry leaves, and ginger (all 97%). The highest Species Medicinal Use Values were recorded, in descending order, for turmeric, ginger, fenugreek seeds, clove, cinnamon, curry leaves, and Tulsi. Contrary to expectations, there was no significant association between years resident in the United States and decreasing use of herbs and spices. Indeed, in some cases the confluence of northern and southern Indian immigrant women with a new identity simply as “Indian” resulted in an increase in the knowledge and use of herbs and spices. Spices are nearly all locally sourced, and where specific herbs are not readily accessible, they are cultivated in homegardens or brought directly from India. Many Indian immigrants are relatively prosperous and able to travel frequently to and from India, thus maintaining close cultural ties with their homeland. Indian immigrant women are fully aware of the health benefits associated with the use of traditional herbs and spices, and all participants reported that Indian food is a healthier choice than American cuisine. Knowledge is passed via vertical transmission, primarily through mothers and grandmothers to daughters. Overall, there is little concern among female Indian immigrants to southern California that knowledge and use of their traditional herbs and spices are in a state of decline.